2000
DOI: 10.1093/oxfordjournals.bja.a013586
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and general anaesthesia in children undergoing MRI and CT: adverse events and outcomes

Abstract: Quality assurance data were collected prospectively for children who were sedated (n = 922) or given general anaesthesia (n = 140) for magnetic resonance imaging (MRI) or computerized tomography (CT). The data included patient characteristics, concurrent medication, adequacy of sedation, adverse events and requirement for escalated care. The quality of scans was evaluated. Reasons for preselection of general anaesthesia included previously failed sedation (28%), potential for failed sedation (32%) and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
253
5
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(280 citation statements)
references
References 0 publications
8
253
5
11
Order By: Relevance
“…In our opinion, general anaesthesia with paralysis and controlled ventilation offers several advantages over intravenous sedation in infants and young children. These patients with limited cardiovascular reserve and cyanotic CHD are prone to desaturate to lower levels in the event of sedation induced respiratory depression or airway obstruction [10]. Besides, effects of sedation can be unpredictable and some of the drug combinations may be associated with delayed recovery.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, general anaesthesia with paralysis and controlled ventilation offers several advantages over intravenous sedation in infants and young children. These patients with limited cardiovascular reserve and cyanotic CHD are prone to desaturate to lower levels in the event of sedation induced respiratory depression or airway obstruction [10]. Besides, effects of sedation can be unpredictable and some of the drug combinations may be associated with delayed recovery.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some problems with MR imaging which pose risks to the medical personnel and patients. 13,18) In 2009, the ASA formulated suggestions for the safe management of iMR imaging, 16) and showed that iMR imaging could increase the core body temperature of the patients. MR imaging could increase the core body temperature by 0.3-0.79 C in patients under sedation or general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging could increase the core body temperature by 0.3-0.79 C in patients under sedation or general anesthesia. 5,13) To evaluate the energy absorbed by the human body, the concept of absorption of radio frequency energy has been proposed (specific absorption rate: SAR). SAR refers to the radiofrequency energy that a unit weight of the human body absorbs within a unit time.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, sedation is not sufficient, so it is necessary to introduce the patient in a short-term general anesthesia. In addition to the possible side effects of anesthesia [16] [17] there are also additional costs due to a disrupted and reduced working process (workflow), limited ability of the patient to cooperate and the spent time intended for imaging [18].…”
Section: Introductionmentioning
confidence: 99%